Insights into Genetic Characteristics and Virological Features of Endemic Avian Influenza A (H9N2) Viruses in Egypt from 2017–2021 - El Sayes, Mohamed; Kandeil, Ahmed; Moatasim, Yassmin; El Taweel, Ahmed; Rubrum, Adam; Kutkat, Omnia; Kamel, Mina Nabil; Badra, Rebecca; Barakat, Ahmed B.; McKenzie, Pamela P.; El-Shesheny, Rabeh; Webby, Richard J.; et al. (Viruses, 2022)
From 2010 to 2013, genotype I avian influenza A(H9N2) viruses of the G1-lineage were isolated from several poultry species in Egypt. In 2014, novel reassortant H9N2 viruses were detected in pigeons designated as genotype II. To monitor the subsequent genetic evolution of Egyptian A(H9N2) viruses, we characterized the full genomes of 173 viruses isolated through active surveillance from 2017 to 2022. In addition, we compared the virological characteristics and pathogenicity of representative viruses. Phylogenetic analysis of the HA indicated that all studied sequences from 2017–2021 were grouped into G1-like H9N2 viruses previously detected in Egypt. Phylogenetic analysis indicated that the Egyptian A(H9N2) viruses had undergone further reassortment, inheriting four genes (PB2, PB1, PA, NS) from genotype II, with their remaining segments deriving from genotype I viruses (these viruses designated as genotype III). Studying the virological features of the two most dominant genotypes (I and III) of Egyptian H9N2 viruses in vitro and in vivo indicated that both replicated well in mammalian cells, but did not show any clinical signs in chickens, ducks, and mice. Monitoring avian influenza viruses through surveillance programs and understanding the genetic and antigenic characteristics of circulating H9N2 viruses are essential for risk assessment and influenza pandemic preparedness.